COD removal from thin-film transistor-liquid crystal display (TFT-LCD) wastewater using chitosan-coated bentonite (CCB) - Ligaray, Mayzonee V. (College of Engineering, University of the Philippines Diliman, 2013)
TFT-LCD is used as display for computers, televisions, and cellular phones. The processes in this industry involve organic compounds that degrade slowly such as monoethanolamine (MEA) and tetra-methyl ammonium hydroxide (TMAH) and a lot of solvents and pigments to enhance the color of the displays. The complex mixture of the chemicals, which have an adverse effect if released to the environment, has high levels of COD and color and very low transparency, indicating bad water quality. In this research, adsorption using chitosan coated bentonite as adsorbent was used in removing the said pollutants. Adsorption is an effective method in reducing the COD content of various kinds of wastewater. It is a simple process and has easy operational conditions however; very few studies investigated its application to TFT-LCD wastewater. This study investigated the effects of selected parameters on the reduction of COD and color from real thin film transistor -- liquid crystal (TFT-LCD) wastewater using chitosan-coated bentonite (CCB). BET surface area analysis, SEM, TGA, and FTIR were performed for the characterization of CCB. Contact time, mass of CCB, pH, and temperature were varied for the batch adsorption experiments. The results revealed that increasing the contact time and mass of CCB increases the % COD removal to its maximum value of 74%, lowering the pH increased the % color removal to almost 100% while the optimized values of the parameters achieved a removal efficiency of 71%. Adsorption using CCB also proved to yield a clear clear effluent at pH 4. Optimization using response surface methodology (RSM) was also implemented to maximize the removal percentages. The optimization experiments were designed by central composite design (CCD). The optimized parameters obtained were 20 h (contact time), 0.8 g (CCB dosage), pH 4, and 30⁰C (temperature). The adsorption experiments also showed that the COD/CCB system best fits the Langmuir isotherm with a correlation coefficient of 0.998 while kinetic studies indicate that chemisorption is the rate-determining mechanism. Thermodynamic studies determined that adsorption of COD on CCB was spontaneous and exothermic. Its enthalpy value reveals that physical adsorption mechanism. Randomness in the solution was also observed from its positive entropy value of 5.5288 J/mol-K indicating that CCB has an attraction to COD compounds.